Hukum Menerima Titipan dan Tata Cara Menjaga Barang dalam Akad Wadi’ah menurut Perspektif Ulama Fiqh - Jaidil kamal (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
AbstractThis writing aims to analyze the concept of the Wadi’ah contract related to the law of receiving and the procedures for maintaining the goods deposited in the wadi'ah contract according to the perspective of fiqh scholars. The scholars of the madhhab of fiqh view that it is an obligation to keep the goods deposited in the wadi'ah contract. Safeguarding the deposited goods is a form of debt in accepting the trust that the giver of the deposit has entrusted. This care is carried out by the person who receives the deposit independently or may also be assisted by another person who is still within the scope of his residence. There was a difference of opinion among the scholars regarding the issue of how to safeguard the goods deposited in the wadi'ah contract. Hanafi and Hambali scholars stated that the party entrusted with it should take care of the goods as if they were their own by trying their best. The Hanafi and Maliki scholars also state that assigned people may ask for the help of others to keep the deposit in the place of those who are their dependents. Meanwhile, scholars from the Shafi'i school stated that the entrusted person is obliged to take care of the deposited item himself.Keywords: Wadi'ah, Fiqh Scholars, Deposits